CONSEQUENCES OF POVERTY FOR INDIVIDUALS AND SOCIETY - Ruslan M. Kliuchnyk (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article examines the main consequences of poverty for individual citizens and society as a whole. Among the consequences of poverty for individuals, physiological, psychological and communicative effects are distinguished. The physiological consequences of poverty are the unavailability of quality food, as well as quality medical, hygiene, and health services, which reduces both life expectancy and health in general. Psychological problems include stress, depression, alcohol and drug abuse, which can lead to suicidal tendencies. The communicative consequences mean that a poor person often loses social ties, and his or her circle of communication becomes quite limited. Poverty also affects society as a whole. Among the purely economic consequences, we singled out the Vicious Cycle of Poverty, to which many Western studies are devoted. Also, impoverished societies in general cannot afford goods and services that are not related to survival. Therefore, there is a low demand for various categories of services, in particular, educational ones. Poverty is one of the factors of labor migration, which is illustrated by the example of Ukraine. In the conditions of a transitional and a market economy in post-Soviet states, the desire to withstand competition on the world market under the conditions of high energy and material intensity of production has been reflected in the preservation of low labour costs. Low wages, in turn, are a direct factor in the formation of social and economic risks in the field of human development. Poverty is also associated with the phenomenon of social exclusion, which we consider as the process of excluding an individual or a social group from social relations. A special class of precariat is being formed. The precariat is capable of self-organization under certain conditions. This group of people is associated with the spread of shadow employment and other forms of violation of the law. Political problems caused by poverty are also important. Poor citizens in the vast majority of countries (at least in all democracies) have the right to vote. Accordingly, they often support populist movements. Poverty and unemployment lead people to support far-left and far-right parties. Far-right movements often have an anti-immigrant focus. Sometimes poverty, social exclusion, social deprivation and other related socio-economic factors lead to revolutions and coups. In our opinion, relative poverty is unavoidable in principle, since in any society there will always be more and less wealthy citizens. But absolute poverty, which puts a person on the edge of normal existence, can and must be overcome. According to this, most countries of the world, including Ukraine, declare themselves welfare states. The article uses the achievements of economic, political, sociological, psychological and other sciences, taking into account the interdisciplinary synthesis and the pluralism of approaches. Modern trends in the interpretation of the consequences of poverty, which can be traced in the works of Ukrainian and foreign authors, are analyzed.